Anti-Bacterial effect, fluoride release, and compressive strength of a glass ionomer containing silver and titanium nanoparticles - Mariem O Wassel; Gehan G Allam (Indian Journal of Dental Research, 2022)
Background: Many attempts have been made to enhance the anti-cariogenic properties of the conventional glass ionomer through incorporation of variable materials. However, most importantly, the incorporation of such materials should not jeopardise the physical or mechanical properties of the final restoration. Aims: To investigate the effect of adding silver nanoparticles (Ag-NPs) and titanium dioxide nanoparticles (TiO2-NPs) to conventional glass ionomer cement (GIC) on its anti-bacterial effect against Streptococcus mutans (S. mutans), fluoride ion release, and compressive strength (CS). Settings and Design: This study was an in vitro investigation where 30-disc specimens were prepared in each of the three studied groups. Materials and Methods: The specimens were categorized into the control group (Group C), in which conventional GIC was used, and Group Ag and Group Ti, in which 5 wt% of Ag-NP and TiO2-NP were added, respectively, to GIC powder. In each group, the anti-bacterial effect against S. mutans, fluoride ion release at 24 hours and 14 and 28 days, and CS were assessed. Data were analysed using one-way analysis of variance, followed by Tukey honest significant difference post-hoc test. Results: Both Ag and Ti groups showed a significantly higher anti-bacterial effect than the control group. Ag-NP increased fluoride ion release, whereas TiO2-NP decreased fluoride release; however, cumulative ion release of both experimental groups did not differ significantly compared to the control group. Adding Ag-NP and TiO2-NP increased CS, yet only the Ti group showed the highest CS mean value that was statistically significant compared to other groups. Conclusions: Adding 5 wt% TiO2-NP or Ag-NP to conventional GIC significantly increased its anti-bacterial effect and its CS without affecting fluoride release.